Assessing Classic Maya multi-scalar household inequality in southern Belize. - Amy E Thompson; Gary M Feinman; Keith M Prufer (PLoS ONE, 2021)
Inequality is present to varying degrees in all human societies, pre-modern and contemporary. For archaeological contexts, variation in house size reflects differences in labor investments and serves as a robust means to assess wealth across populations small and large. The Gini coefficient, which measures the degree of concentration in the distribution of units within a population, has been employed as a standardized metric to evaluate the extent of inequality. Here, we employ Gini coefficients to assess wealth inequality at four nested socio-spatial scales-the micro-region, the polity, the district, and the neighborhood-at two medium size, peripheral Classic Maya polities located in southern Belize. We then compare our findings to Gini coefficients for other Classic Maya polities in the Maya heartland and to contemporaneous polities across Mesoamerica. We see the patterning of wealth inequality across the polities as a consequence of variable access to networks of exchange. Different forms of governance played a role in the degree of wealth inequality in Mesoamerica. More autocratic Classic Maya polities, where principals exercised degrees of control over exclusionary exchange networks, maintained high degrees of wealth inequality compared to most other Mesoamerican states, which generally are characterized by more collective forms of governance. We examine how household wealth inequality was reproduced at peripheral Classic Maya polities, and illustrate that economic inequity trickled down to local socio-spatial units in this prehispanic context.